Auto Immune Mixed Haemolytic anaemia: A rare presentation of SLE - Srikanth, Mote; Lokesh, S.; Dutta, Anirban; Danasekaran, Vaishnavi (International Journal of Advances in Medicine, 2019)
Auto Immune Mixed Haemolytic Anaemia (AIHA) is defined as presence of both warm and cold antibodies against patient’s own red blood cells which is diagnosed by monospecific Direct anti-globulin test. Hereby we report a middle-aged women old women who was a known case of hypothyroidism on regular medication, presented with history of fatigability, exercise intolerance and exertional breathlessness of 1 month duration. The patient was subjected for preliminary investigations, which revealed severe anaemia with hemoglobin of 3.6 g% and an increased reticulocyte count of 12% with normal total leukocyte and platelet counts. Peripheral smear revealed anisopoikilocytosis, nucleated RBCs and schistocytes. Biochemical tests for haemolysis was evaluated which showed and elevated LDH levels (780U/L), and a reduced serum haptoglobulin levels. Liver Function test revealed a total bilirubin of 6.8mg/dl with indirect bilirubin of 5.4 mg/dl with normal liver enzymes. Baseline evaluation of Auto immune haemolytic anaemia with coombs test turned out to be positive. Patient was subjected for Mono specific DAT, Indirect Anti-globulin test (IAT) and antibody screening. Mono specific DAT showed both Anti IgG and anti C3 antibodies. IAT test was positive at 4⁰C and negative at 22⁰C and 39⁰C which confirmed that the AIHA was of mixed warm and cold type. On evaluation for connective tissue diseases, patient serum was reactive for ANA and ds-DNA and found to have Systemic Lupus Erythematosus which is a rarity and was responded to corticosteroids.